Numerical solution of time-dependent advection-diffusion-reaction equations - Hundsdorfer Willem; Verwer Jan (Berlin Springer-Verlag, 2003)
This book describes numerical methods for partial differential equations (PDEs) coupling advection, diffusion and reaction terms, encompassing methods for hyperbolic, parabolic and stiff and nonstiff ordinary differential equations (ODEs). The emphasis l
Keywords: Partial differential equations; Partial differential equations-numerical solutions